Easy Preparation of Electrode Surfaces with Dispersed Size-Controlled Au Nanoparticles by Electrodeposited PPI-Dendrimers as Templates. Issue 6 (20th April 2017) - Villena, Carlos; Losada, José; Alonso, Beatriz; Casado, Carmen M.; Armada, M. Pilar García
Abstract : The main target of this work is the preparation of nanostructurated surfaces with size-controlled gold nanoparticles to obtain effective electrocatalytic surfaces. In this paper, we show that dispersed Au nanoparticles (AuNPs) having diameters of less than 3 nm can be synthesized in situ with aminoferrocenyl- and amidoferrocenyl-poly(propyleneimine) (PPI) dendrimers previously electrodeposited onto electrode surfaces. Dendrimers of first, third and fifth generation have been studied and good dispersed non aggregated nanoparticles were obtained in all the cases. In a similar way than in homogeneous media, inter-dendrimer Au nanoparticles have been obtained when first or third generation dendrimer modified electrodes were used, while smaller nanoparticles were obtained with fifth generation dendrimer, indicating that intra-dendrimer Au nanoparticles have been synthesized. The AuNPs were obtained from a HAuCl4 solution after chemical reduction with NaBH4 . The formation of AuNPs was followed by UV-Vis spectroscopy; electrochemistry and ultra-high resolution scan electron microscopy (HRSEM). The obtained electrodes have been successfully used for the tetraelectronic oxygen reduction reaction (ORR) with a low onset potential (0.00 V vs. SCE), high kinetic current densities and also high heterogeneous electron transfer rate constants.